DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Yusupova Maftuna; Jalolava M (TADQIQOTLAR, 2025)
Annotation: This article explores the various challenges educators face when teaching foreign languages to young learners. It highlights linguistic, psychological, and pedagogical difficulties, such as short attention spans, limited first-language grammar knowledge, classroom management, maintaining learner motivation, and assessing progress. The article also discusses the role of parental involvement and proposes effective strategies to address these challenges.